Training Load and Current Soreness Predict Future Delayed Onset Muscle Soreness in Collegiate Female Soccer Athletes - Brett S. Pexa; Christopher J. Johnston; Jeffrey B Taylor; Kevin R. Ford (North American Sports Medicine Institute, 2023)
# Background Delayed onset muscles soreness (DOMS) is an indication of muscle stress and trauma that develops from excessive musculoskeletal loads. Musculoskeletal loads can be measured with wearable devices, but there is limited research on specific training load metrics that most correlate with DOMS after activity. # Purpose To determine the predictive capabilities of training load variables on the development of lower extremity DOMS in female collegiate soccer athletes throughout an entire season. # Study Design Prospective Cohort # Methods Twenty-seven collegiate female soccer athletes reported their lower extremity DOMS each day prior to all soccer activity. Participants wore Polar heart rate and global positioning monitors to capture training load measures. Pearson correlation coefficients were used to assess the relationships between the training load variables and change in DOMS when collapsed across dates. Separate linear mixed models were performed with the following day's DOMS as the outcome variable, training load and the current day's DOMS as predictor variables, and participants serving as random intercepts. # Results All training load variables significantly predicted change in DOMS, with number of decelerations (ρ=0.72, p \<0.001), minutes spent at greater than 80% of maximum heart rate (HRmax) (ρ=0.71 , p \<0.001), and distance (ρ=0.70 , p \<0.001) best correlating with change in DOMS. Linear mixed models revealed a significant interaction of all training load and current day's DOMS on the following day's DOMS (p\<0.001), but number of decelerations, HRmax, and total number of accelerations demonstrated the highest coefficient of determination (R^2^ marginal=33.2% - 29.2% , R^2^ conditional= 46.9% - 44.8%). # Conclusions Training load variables paired with the current day's DOMS significantly predict lower extremity DOMS in the future, with number of decelerations, accelerations, and HRmax best predicting future DOMS. Although this demonstrates that training load variables predict lower extremity DOMS, future research should incorporate objective measures of strength or jump kinetics to identify if similar relationships exist. # Level of Evidence Level 3